Two new species of ground-dwelling Cyrtodactylus (Geckoella) from the Mysore Plateau, south India - Agarwal, Ishan (Zootaxa, 2016)
Two new species of ground-dwelling geckos of the genus Cyrtodactylus (Geckoella) are described from the Mysore Plateau, in southern India. The new species are members of the C. collegalensis species complex, with 8.7 % uncorrected ND2 sequence divergence from each other and greater than 10 % divergence from described members of the C. collegalensis complex, from which they differ in subtle aspects of colour pattern and morphometric ratios. The type localities of the new species are 130 km apart, and 100 km and 225 km from the type locality of C. collegalensis in the Biligiriranga Hills. The discovery of these new species in isolated mountains within a small area suggests other high elevation areas in the region may have undescribed species, and a redefinition of biodiversity patterns in peninsular India.